Joint Analysis of Genome-Wide Association Data Reveals No Genetic Correlations Between Low Back Pain and Neurodegenerative Diseases - Wu, Pengfei; Du, Bing; Wang, Bing; Yin, Rui; Lv, Xin; Dai, Yuliang; Zhang, Wan; Xia, Kun (Frontiers in Genetics, 2021)
Background: We aimed to explore the genetic correlation and bi-directional causal relationships between low back pain (LBP) and three neurodegenerative diseases, Alzheimer's disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). Methods: Summary-level statistics were obtained from genome-wide association studies of LBP (n = 177860), AD (n = 63926), PD (n = 482730) and ALS (n = 80610). We implemented linkage disequilibrium score regression to calculate heritability estimates and genetic correlations. To investigate possible causal associations between LBP and three neurodegenerative diseases, we also conducted a bi-directional two-sample Mendelian randomization (MR) study. Inverse variance weighted MR was employed as the primary method to generate overall estimates, whereas complementary approaches and sensitivity analyses were conducted to confirm the consistency and robustness of the findings. Results: There was no evidence of genetic correlations between LBP and AD (Rg = -0.033, P = 0.766). MR analyses did not support the causal effect of LBP on AD (OR = 1.031; 95% CI, 0.924–1.150; P = 0.590), or the effect of AD on LBP (OR = 0.963; 95% CI, 0.923–1.006; P = 0.090). Likewise, this study failed to identify genetic correlations between LBP and two other neurodegenerative diseases. MR results of the associations of LBP with PD and ALS, and the reverse associations, did not reach Bonferroni-corrected significance. Conclusion: The study did not support genetic correlations or causations between LBP and three common neurodegenerative diseases, AD, PD and ALS in the European population.